-34=v+42-5y

Simple and best practice solution for -34=v+42-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -34=v+42-5y equation:


Simplifying
-34 = v + 42 + -5y

Reorder the terms:
-34 = 42 + v + -5y

Solving
-34 = 42 + v + -5y

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-1v' to each side of the equation.
-34 + -1v = 42 + v + -1v + -5y

Combine like terms: v + -1v = 0
-34 + -1v = 42 + 0 + -5y
-34 + -1v = 42 + -5y

Add '34' to each side of the equation.
-34 + 34 + -1v = 42 + 34 + -5y

Combine like terms: -34 + 34 = 0
0 + -1v = 42 + 34 + -5y
-1v = 42 + 34 + -5y

Combine like terms: 42 + 34 = 76
-1v = 76 + -5y

Divide each side by '-1'.
v = -76 + 5y

Simplifying
v = -76 + 5y

See similar equations:

| 2x^2-2x=180 | | 7-(6a+11)=38 | | 4y=80 | | x^2+9x-3375=0 | | 5x+2.15=11 | | g-6=56 | | 2(m-4)=5m+7 | | -5n^2-26+40=0 | | 3(4-x)=x+2(x+3) | | 8x+2+5x+7=12x+4 | | 2x-6/4=2x | | 9x^2-2=3x | | 2x-6/4=2x-2 | | 98-4b=-11b-14 | | -3m=5(2-m) | | 2(m-4)=5m | | 9b-3/9=5b+5/3 | | (3x+1)(2x+1)= | | -2(p-4)=14 | | 2*0.5z+7= | | 6x-3=5x+17 | | 2x-6/4=2x-16/2 | | -2(a+6)+8=-(6+4a) | | -(6m+5)=25 | | x-4/5=x/9 | | 7-n=9 | | 12/60=1 | | 2(x+6)=3x | | y+3/7=y-3/4 | | 6(v+2)=2(8+2v) | | 17(12x-48)=-5100 | | -5(4x-3)= |

Equations solver categories